Groundwater identification using geophysical tools and its implications for the stability of slopes in an open pit mine - Duz, Beatriz Guzzo [UNESP]; Moreira, César Augusto [UNESP]; Hartwig, Marcos Eduardo; Miano, Felipe Queiroz [UNESP]; Araújo, Ana Flávia [UNESP] (Universidad Nacional Autonoma de Mexico, 2024)
The open pit mining development begins with the opening of pits with the rock mass excavation and formation of slopes and berms for ore exploration. Knowledge about the geological conditions represents an important step in this process, since rock masses generally have heterogeneous characteristics and the presence of discontinuities can become an aggravating factor in the safety of operations. The characterization and classification of these discontinuities, as well as the identification of the groundwater in the rock mass, has a great importance to ensure the safety of operations during the mine’s production process, in addition to ensure the effectiveness of its decommissioning process. The use of DC resistivity geophysical method has been increasing to characterization and identification lithological types and presence of water, since it is a non-invasive research tool with fast ability to obtain data. DC resistivity together with visual investigation methods, such as obtaining the discontinuities orientation and their alteration characteristics, provides important information for the characterization of the rock mass. Given this importance, the present work aimed to use DC resistivity to identify the presence of water and its correlation with lithology and rock mass structure in order to identify how these variables influence the occurrence of ruptures. To this end, two-dimensional resistivity sections were designed and related to visual inspection data and kinematic analyzes obtained from structural data of the rock mass. The integration of these results indicated that the ruptures present in the investigated mine slopes are related to zones whose predominant lithology is volcanic breccia with the presence of water in the subsurface. These ruptures compromise the stability of the slopes and consequently make the decommissioning mine process difficult.
Keywords: acuífero; análisis estructural; aquifer; DC resistivity; geofísica; geophysics; resistividad eléctrica; rupturas; ruptures; structural analyses